Evolving Global Linkage : A Time-Varying Analysis of the Indian Stock Market - Routh, Bishal; Sarkar, Joy; Paul, Raju (Indian Journal of Finance, 2026)
Purpose : To address the time-varying integration of the Indian stock market and to understand the true nature of domestic returns and their alignment with the global market. If misaligned, what could be the causes? Methodology : The International Capital Asset Pricing Model framework proposed by Levine and Zervos was used to estimate the Market Integration Index. The index was further extended to a time-varying parameter using the Kalman Filter. Findings : Domestic returns consistently outperformed global returns. It was found that 60% of the return was aligned to domestic factors; thus, only 40% was sensitive to global factors. The Kalman filter showed that the Indian stock market was deviating from the global market between 2012 and 2025, with two rare instances of co-movement. Practical Implication : The positive and significant α0, together with β0 > 1, suggested the existence of a low-beta anomaly, implying that investors can earn higher returns at relatively lower risk, which enhances the attractiveness of the Indian stock market. Originality : Numerous studies have investigated the integration of the Indian stock market with global markets; however, they have used fixed coefficient models, which did not capture the true dynamics of market integration, which is time-varying in nature. Hence, the Kalman filter, a state-space technique that allows parameters to vary across time, was used with the international capital asset pricing model to unveil the same. The study used the latest period from January 2012 to July 2025; hence, it would meet the needs of the current crop of investors.